2017
DOI: 10.1007/s11682-017-9681-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain white matter structural networks in patients with non-neuropsychiatric systemic lupus erythematosus

Abstract: Previous neuroimaging studies have revealed cognitive dysfunction in patients with systemic lupus erythematosus (SLE) and suggested that it may be related to disrupted brain white matter (WM) connectivity. However, no study has examined the topological properties of brain WM structural networks in SLE patients, especially in patients with non-neuropsychiatric SLE (non-NPSLE). In this study, we acquired DTI datasets from 28 non-NPSLE patients and 24 healthy controls, constructed their brain WM structural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
3
15
1
Order By: Relevance
“…Results similar to ours were reported in a recent DTI study showing that non-NP SLE patients had widespread reduction in brain connectivity even with no NP symptoms. 53 Other data supporting this notion come from our study of SLE patients who had increased cortical activation on functional MRI during the performance of working memory and executive function tasks, interpreted as evidence of compensatory cortical activation in the presence of early WM neuropathology. 40 The strengths of this study include the first use of DTI and neuropsychological testing in SLE using a longitudinal design, careful patient selection to exclude any NP SLE or other major disorders, and thorough medical surveillance.…”
Section: Discussionmentioning
confidence: 67%
“…Results similar to ours were reported in a recent DTI study showing that non-NP SLE patients had widespread reduction in brain connectivity even with no NP symptoms. 53 Other data supporting this notion come from our study of SLE patients who had increased cortical activation on functional MRI during the performance of working memory and executive function tasks, interpreted as evidence of compensatory cortical activation in the presence of early WM neuropathology. 40 The strengths of this study include the first use of DTI and neuropsychological testing in SLE using a longitudinal design, careful patient selection to exclude any NP SLE or other major disorders, and thorough medical surveillance.…”
Section: Discussionmentioning
confidence: 67%
“…Bernardo et al [59] revealed that SLE patients with memory impairment showed reduced cortical thickness in the precentral gyrus when compared to the SLE patients without memory deficits. Previous diffusion tensor imaging study demonstrated lower fractional anisotropy in the precentral gyrus in SLE patients [60]. Sensorimotor network (SMN), including the postcentral gyrus and precentral gyrus, is one of the earliest resting brain network proposed in the fMRI study [16].…”
Section: Discussionmentioning
confidence: 99%
“…27 Only a limited number of studies have previously focused on the association between cognitive function and brain volumes on MRI in patients with SLE without major nervous system involvement ('non-NPSLE'). [28][29][30][31][32][33][34][35][36][37] Several studies found an association between global cognitive impairment and reduced grey matter 36 or white matter volume 28 30 36 and in one study this association was not found. 31 In our study, we demonstrated that brain volumes were indeed associated with cognitive function (all domains) in patients with SLE, but differences were present between NPSLE phenotypes.…”
Section: Lupus Lupus Lupusmentioning
confidence: 96%